Freshwater planarians (Platyhelminthes, Tricladida) from the Iberian Peninsula and Greece: diversity and notes on ecology - Vila-Farré, Miquel; Sluys, Ronald; Almagro, Ío; Handberg-Thorsager, Mette; Romero, Rafael (Zootaxa, 2011)
Few studies have examined the diversity of freshwater planarians in the Iberian Peninsula and Greece. We have searched extensively for specimens, mainly in the Iberian Peninsula, and have gathered information on their taxonomy and biogeography. Two new species of Dendrocoelum and six new species of Phagocata are described. We also review the status of five other species and present distribution maps that summarize records of freshwater planarians in the Iberian Peninsula. The diversity of three ecological groups of freshwater planarians in this area is discussed and we show that it has a rich, stream-dwelling freshwater triclad fauna, contrary to the findings of earlier studies. But our findings support the traditional viewpoint that European lake-dwelling species are scarce in Spain. The distribution pattern of Girardia tigrina is also discussed. We conclude that the critical status of Schmidtea mediterranea in this area is partly due to habitat alteration through human interference.